A Parasite Rescue and Transformation Assay for Antileishmanial Screening Against Intracellular Leishmania donovani Amastigotes in THP1 Human Acute Monocytic Leukemia Cell Line - Jain, Surendra K. (MyJove Corporation, 2012)
Leishmaniasis is one of the world's most neglected diseases, largely affecting the poorest of the poor, mainly in developing countries. Over 350 million people are considered at risk of contracting leishmaniasis, and approximately 2 million new cases occur yearly(1). Leishmania donovani is the causative agent for visceral leishmaniasis (VL), the most fatal form of the disease. The choice of drugs available to treat leishmaniasis is limited (2);current treatments provide limited efficacy and many are toxic at therapeutic doses. In addition, most of the first line treatment drugs have already lost their utility due to increasing multiple drug resistance (3). The current pipeline of anti-leishmanial drugs is also severely depleted. Sustained efforts are needed to enrich a new anti-leishmanial drug discovery pipeline, and this endeavor relies on the availability of suitable in vitro screening models. In vitro promastigotes (4) and axenic amastigotes assays(5) are primarily used for anti-leishmanial drug screening however, may not be appropriate due to significant cellular, physiological, biochemical and molecular differences in comparison to intracellular amastigotes. Assays with macrophage-amastigotes models are considered closest to the pathophysiological conditions of leishmaniasis, and are therefore the most appropriate for in vitro screening. Differentiated, non-dividing human acute monocytic leukemia cells (THP1) (make an attractive) alternative to isolated primary macrophages and can be used for assaying anti-leishmanial activity of different compounds against intracellular amastigotes. Here, we present a parasite-rescue and transformation assay with differentiated THP1 cells infected in vitro with Leishmania donovani for screening pure compounds and natural products extracts and determining the efficacy against the intracellular Leishmania amastigotes. The assay involves the following steps: (1) differentiation of THP1 cells to non-dividing macrophages, (2) infection of macrophages with L. donovani metacyclic promastigotes, (3) treatment of infected cells with test drugs, (4) controlled lysis of infected macrophages, (5) release/rescue of amastigotes and (6) transformation of live amastigotes to promastigotes. The assay was optimized using detergent treatment for controlled lysis of Leishmania-infected THP1 cells to achieve almost complete rescue of viable intracellular amastigotes with minimal effect on their ability to transform to promastigotes. Different macrophage:promastigotes ratios were tested to achieve maximum infection. Quantification of the infection was performed through transformation of live, rescued Leishmania amastigotes to promastigotes and evaluation of their growth by an alamarBlue fluorometric assay in 96-well microplates. This assay is comparable to the currently-used microscopic, transgenic reporter gene and digital-image analysis assays. This assay is robust and measures only the live intracellular amastigotes compared to reporter gene and image analysis assays, which may not differentiate between live and dead amastigotes. Also, the assay has been validated with a current panel of anti-leishmanial drugs and has been successfully applied to large-scale screening of pure compounds and a library of natural products fractions (Tekwani et al. unpublished).